Quantifying hypoxia with diffuse reflectance spectroscopy for advanced prognostication and real-time response monitoring in rectal cancer: an in vivo feasibility study - Fletcher,T; Monfort-Sanchez,E; Keshavarz,M; Avery,J; Ashrafian,H; Darzi,AW; Thompson,AJ (SPIE, 2023)
Tumour hypoxia is a critical factor in treatment failure and resistance, and its accurate measurement with diffuse reflectance spectroscopy (DRS) could be used for prognostic and response monitoring purposes. In this in vivo characterisation study, we sequentially measured oxygenation trends over the entire course of tumour growth in mice using a multi-depth, fibre-optic DRS probe. Results demonstrated a clear downtrend in oxygenation over time. This progression was not always linear, with significant heterogeneity over time and between mice. Our findings will be further validated against gold standards prior to investigating whether hypoxia can be used to predict radiotherapy responses.